# Thread: simplifying an expression with exponents, such that x=-1

1. ## simplifying an expression with exponents, such that x=-1

If I want to simplify the following expression such that x= -1:

-9x2 - x + 1
___________
x3 + x

How do I input the value of -1 into -9x2?

like this -9(-1)2 which simplifies to -9(1) which equals -9

or like this -9(-12) which simplifies to -9(-1) which equals positive 9

I ask this because I know that exponents only apply to the value or parenthetical expression right next to it. In the former case, (-1) times (-1) is positive 1. In the latter case, the square only applies to the 1 and not to the minus sign which is then left over after the 1 is squared. So, this yields a -1.

So, which way is right??

2. ## Re: simplifying an expression with exponents, such that x=-1

$x^{2}$ is shorthand notation for $x$ multiplied by $x.$
Substitute $x=-1$ and you get $x^{2}=x.x=(-1).(-1)=1$

3. ## Re: simplifying an expression with exponents, such that x=-1

$-9(-1)^2$

evaluate exponents first ...

$-9(1)$

then multiply ..

$-9$

4. ## Re: simplifying an expression with exponents, such that x=-1

Originally Posted by skeeter
$-9(-1)^2$
$-9(1)$
$-9$